PENGARUH PUPUK N, P, K DAN PUPUK ORGANIK CAIR (POC) TERHADAP PERTUMBUHAN, HASIL DAN EFISIENSI PRODUKSI TANAMAN PADI GOGO (Oryza sativa L.) DI MEDIUM TANAH ULTISOL - Habibullah, Muhammad; ', Idwar; ', Murniati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The research was conducted in the greenhouse of the Faculty of agriculture, University of Riau, Pekanbaru Campus Binawidya Km 12.5 From April until September 2014. Trial using completely randomized design (CRD) factorial. First factor fertilizer N, P, K consists of 5 levels (0 g/polybag, 0.17 N, 0.09 P2O5,0.11K2O g/polybag, 0.35 N, 0.18P2O5, 0.23K2O g/polybag, 0.52N, 0.27P2O5, 0.34K2O g/polybag and 0.69N, 0.36P2O5,0.45K2O g/polybag) and OLF the second factor consists of 3 levels (0 ml, 350 ml and 700 ml/polybag). Treatment was repeated 3 times. Data results were analyzed statistically operates with anova and Duncan test continued level of 5%. The observed parameters is high plant, tillers maximum term, term productive tillers, harvest, long panicles per clump, clump of grain per time period, weight dry milled grain, percentage of grain pithy, weight of 100 grains, the efficiency of production and the effect of OLF differences efficiency of N, P, K. Results indicate combination of 0.69N, 0.36P2O5, 0.45K2O g/polybagwith OLF 700 ml/polybag increase high plant, tillers maximum term, term productive tillers, age harvest, long panicles per clump, period of grains per panicle, percentage of grain pithy, dry milled grain weight and production efficiency. Â  Keywords: upland rice, N, P, K, liquid organic fertilizer, production efficiency.